MXene-based separators for redox-enhanced electric capacitors with a suppressed shuttle effect and self-discharge: the effect of MXene ageing - Han, Qiankun; Yang, Wei; Li, Wenshi; Wu, Maosheng; Yao, Jing; Zhao, Man; Lu, Xianmao (New journal of chemistry, 2023)
The application of MXenes in redox-enhanced electrochemical capacitors (Redox ECs) for suppressing self-discharge caused by the shuttling of redox species in the electrolyte has proved to be promising. However, the success of this strategy is highly dependent on the MXene layered structure that provides tunable spacing for polyiodide confinement in iodide-based redox ECs. Therefore, the ageing of the MXene which leads to expanded interlayer spacings and thus reduced confinement of redox ions would inevitably affect the ability of the MXene to suppress the shuttle effect and self-discharge. In this study, Ti 3 C 2 T x MXenes with different ageing times are prepared and self-assembled onto commercial glass fiber membranes (GFMs) as separators for iodide-based redox ECs. Self-discharge tests reveal that while the pristine Ti 3 C 2 T x separator delivers a voltage retention of 59% in 24 h, the cell with Ti 3 C 2 T x aged for 12 h exhibited a much lower voltage retention of 15%, indicating much faster self-discharge. This work provides an insight into the effect of ageing on the application of MXenes for reducing the shuttle effect and mitigating self-discharge in redox ECs. The shuttle effect of redox-enhanced electric capacitors cannot be suppressed when MXene-based separators are subject to ageing.